Successful Interview Skills - Rebecca Corfield (Kogan Page, 2004)
Fully updated and including a new section onInternet resources, this new edition of Successful Interview Skills looksat every aspect of the interview process, including: what employers are lookingfor; creating a positive first impression; what to say in interviews; answeringtough interview questions; and how to control nerves. No candidate should riskattending an interview without this concise and helpful guide for theinexperienced and those out of practice.